A cellular automaton model reproducing realistic propagation speed of downstream front of the moving synchronized pattern. Issue 1 (23rd December 2019) - Wang, Zuojun; Ma, Shoufeng; Jiang, Rui; Tian, Junfang
ABSTRACT: The moving synchronized pattern (MSP) is an important traffic pattern that can emerge when traffic breakdown occurs. However, up to now most models cannot reproduce a realistic propagation speed of downstream front of the MSP, which significantly weakens their applications in traffic breakdown prediction and control. In this paper, a new brake light cellular automaton model is proposed, which assumes that: (i) the drivers would be sensitive to the brake light only when their speeds are larger than a critical speed; (ii) the anticipated deceleration of a preceding vehicle increases with the increase of the speed of the following vehicle. Simulation analysis shows that the new model can depict traffic breakdown and related synchronized traffic flow patterns. Importantly, it can realistically reproduce the propagation speed of downstream front of the MSP. Finally, the new model is calibrated and validated by NGSIM detector data.